RightPath: a model of community-based musculoskeletal care for children. Issue 2 (16th October 2020) - Smith, Nicola; Mercer, Victoria; Firth, Jill; Jandial, Sharmila; Kinsey, Katharine; Light, Helen; Nye, Alan; Rapley, Tim; Foster, Helen E
Abstract: Objectives: Musculoskeletal (MSK) presentations are common (reported prevalence of one in eight children) and a frequent cause of consultations (6% of 7-year-olds in a cohort study from the UK). Many causes are self-limiting or raised as concerns about normal development (so-called normal variants). We aimed to describe a new model of care to identify children who might be managed in the community by paediatric physiotherapists and/or podiatrists rather than referral to hospital specialist services. Methods: Using mixed methods, we tested the feasibility, acceptability and transferability of the model in two UK sites. Evaluation included patient flow, referral times, diagnosis and feedback (using questionnaires, focus groups and interviews). Results: All general practitioner referrals for MSK presentations (in individuals <16 years of age) were triaged by nurses or allied health professionals using a triage guide; ∼25% of all MSK referrals were triaged to be managed by community-based paediatric physiotherapists/podiatrists, and most (67%) had a diagnosis of normal variants. Families reported high satisfaction, with no complaints or requests for onward specialist referral. No children re-presented to the triage service or with serious MSK pathology to hospital specialist services in the subsequent 6 months after triage. Triagers reported paediatric experience to be important in triage decision-making and case-based learning to be the preferred training format. Conclusion: The triage model is acceptable, feasible and transferable to enable appropriate care in the community for a proportion of children with MSK complaints. This is a multi-professional model of better working together between primary community and specialist providers.